A Simple Criterion for Equal Value Composition of Capital - Parys, Wilfried (Quarterly Journal of Economics, 1977)
Journal Article A Simple Criterion for Equal Value Composition of Capital Get access Wilfried Parys Wilfried Parys UFSIA, University of Antwerp, Belgium Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 91, Issue 3, August 1977, Pages 511–512, https://doi.org/10.2307/1885983 Published: 01 August 1977